2016
DOI: 10.1016/j.rhm.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Reform of abortion law in Uruguay: context, process and lessons learned

Abstract: In October 2012, a new law was approved in Uruguay that allows abortion on demand during the first 12 weeks of pregnancy, 14 weeks in the case of rape, and without a time limit when the woman's health is at risk or in the case of foetal anomalies. This paper analyses this legal reform. It is based on 27 individual and group interviews with key informants, and on review of primary documents and the literature. The factors explaining the reform include: secular values in society, favourable public opinion, a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
43

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(81 citation statements)
references
References 3 publications
0
38
0
43
Order By: Relevance
“…Indeed, in many places, National Health Service responsibility for service provision continues to be partially achieved by contracting out to NGOs, with Colombia and South Africa relying significantly on provision by national and international NGOs, respectively . Uruguay is the only one of these countries that limits abortion to facilities that belong to the integrated national health system; there is significant private provision alongside public sector provision in all the other countries …”
Section: Recipientsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, in many places, National Health Service responsibility for service provision continues to be partially achieved by contracting out to NGOs, with Colombia and South Africa relying significantly on provision by national and international NGOs, respectively . Uruguay is the only one of these countries that limits abortion to facilities that belong to the integrated national health system; there is significant private provision alongside public sector provision in all the other countries …”
Section: Recipientsmentioning
confidence: 99%
“…Women seeking care are of course the ultimate recipients of these programs. Aside from Portugal and Uruguay, interviewees reported that many women were inadequately informed about safe legal care options and therefore continued to resort to illegal and often unsafe procedures …”
Section: Recipientsmentioning
confidence: 99%
See 3 more Smart Citations